2013
DOI: 10.1167/iovs.13-11871
|View full text |Cite
|
Sign up to set email alerts
|

Transduction of Photoreceptors With Equine Infectious Anemia Virus Lentiviral Vectors: Safety and Biodistribution of StarGen for Stargardt Disease

Abstract: In summary, these studies demonstrate StarGen to be well tolerated and localized following subretinal administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
87
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 28 publications
1
87
0
3
Order By: Relevance
“…It had been noted, however, that the PR transduction by lentiviruses was more efficient in other animals, such as chicken and nonhuman primates (Lotery et al 2002;Williams et al 2006). Subsequently, we were able to show a more efficient PR transduction of the NHP retina by EIAV lentivectors using either GFP (Binley et al 2013) or LacZ (data not shown) as reporters under the constitutive CMV promoter. Transduction of PRs, in addition to RPE, in the injected area of adult macaques suggests that lentiviral vectors can more efficiently transduce PRs in adult NHPs than in mice, thus raising hope for gene therapy in humans, especially for delivering large genes such as ABCA4.…”
Section: Lentiviral Gene Delivery In Abca4-associated Diseasesmentioning
confidence: 91%
“…It had been noted, however, that the PR transduction by lentiviruses was more efficient in other animals, such as chicken and nonhuman primates (Lotery et al 2002;Williams et al 2006). Subsequently, we were able to show a more efficient PR transduction of the NHP retina by EIAV lentivectors using either GFP (Binley et al 2013) or LacZ (data not shown) as reporters under the constitutive CMV promoter. Transduction of PRs, in addition to RPE, in the injected area of adult macaques suggests that lentiviral vectors can more efficiently transduce PRs in adult NHPs than in mice, thus raising hope for gene therapy in humans, especially for delivering large genes such as ABCA4.…”
Section: Lentiviral Gene Delivery In Abca4-associated Diseasesmentioning
confidence: 91%
“…In these studies, there were no abnormal clinical or histopathologic findings in either species. Although antibodies to the vector were detected in rabbits, these findings were not associated with long-term toxicity findings (Binley et al 2013). NCT01367444 is a Phase 1/2 dose escalation safety study of a subretinal injected viral construct identified as SAR422459.…”
Section: Abca4 Gene Therapymentioning
confidence: 97%
“…L'efficacité de transduction des photorécepteurs par les lentivirus dépend de l'origine du lentivirus et de l'espèce étudiée [19]. Par exemple, les lentivirus d'origine équine donnent de bons résultats de transduction des photorécepteurs situés à proximité du site d'injection chez le primate non humain [19,20]. Deux essais cliniques sont en cours pour traiter la 3 épisomale (pour le virus recombinant).…”
Section: Les Lentivirusunclassified